2019
DOI: 10.1002/cjce.23398
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous catalytic condensation reaction of methyl propionate and formaldehyde in a fluidized bed reactor

Abstract: A one-step aldol condensation reaction of methyl propionate and formaldehyde to produce methyl methacrylate is a promising environmentally sustainable strategy. In this work, the aldol condensation reaction was firstly conducted in a fluidized bed reactor using different types of catalysts. Zirconium and cesium-loaded SiO 2 and Al 2 O 3 acid-base bifunctional catalysts were prepared by wetness impregnation. Experimental results demonstrated the 15 % Cs-0.05 %Zr/SiO 2 (100-200 mesh) catalyst exhibited excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The catalytic performance of the prepared catalyst was also compared with other reported results, which confirm the higher activity of our developed catalyst (Table S1). ,,,,, A series of characterization techniques including NH 3 -TPD, CO 2 -TPD, pyridine-FTIR, and XPS were carried out to investigate the intrinsic reason of the increased activity and to build up the potential relationship between the structure and activities in this catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic performance of the prepared catalyst was also compared with other reported results, which confirm the higher activity of our developed catalyst (Table S1). ,,,,, A series of characterization techniques including NH 3 -TPD, CO 2 -TPD, pyridine-FTIR, and XPS were carried out to investigate the intrinsic reason of the increased activity and to build up the potential relationship between the structure and activities in this catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…The internals, as an intrusive device, equipped in BCs have been perceived as an effective method for achieving mass transfer intensification [14][15][16]. Researchers have found that enhancing bubble coalescence and breakup processes in the liquid phase can promote mass transfer [17], and the results show that the significant crests in the mass transfer coefficient coincide with significant crests in the bubble breakup and coalescence rates.…”
Section: Introductionmentioning
confidence: 99%